The Role of Curriculum in Developing Children's Intelligence according to Sayyid Muhammad Qutb: An Islamic Perspective - Hafidzi, Anwar; Ali, Mohd Hatta Mohamed (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
This study aims to explore the concept of curriculum in developing children's intelligence from the perspective of Sayyid Muhammad Qutb. The study is based on a literature review of Qutb's book